Fourier-transform infrared (FT-IR) spectroscopy analysis discriminates asymptomatic and symptomatic Norway spruce trees. (December 2019) - Mukrimin, Mukrimin; Conrad, Anna O.; Kovalchuk, Andriy; Julkunen-Tiitto, Riitta; Bonello, Pierluigi; Asiegbu, Fred O.
Highlights: Samples from naturally infected Norway spruce trees were analyzed by FT-IR. FT-IR spectroscopy can discriminate between healthy and rotten Norway spruce trees. Concentrations of condensed tannins can be predicted based on FT-IR results. Abstract: Conifer trees, including Norway spruce, are threatened by fungi of the Heterobasidion annosum species complex, which severely affect timber quality and cause economic losses to forest owners. The timely detection of infected trees is complicated, as the pathogen resides within the heartwood and sapwood of infected trees. The presence of the disease and the extent of the wood decay often becomes evident only after tree felling. Fourier-transform infrared (FT-IR) spectroscopy is a potential method for non-destructive sample analysis that may be useful for identifying infected trees in this pathosystem. We performed FT-IR analysis of 18 phloem, 18 xylem, and 18 needle samples from asymptomatic and symptomatic Norway spruce trees. FT-IR spectra from 1066 – 912 cm −1 could be used to distinguish phloem, xylem, and needle tissue extracts. FT-IR spectra collected from xylem and needle extracts could also be used to discriminate between asymptomatic and symptomatic trees using spectral bands from 1657 – 994 cm −1 and 1104 – 994 cm −1, respectively. A partial least squares regression model predicted the concentration of condensed tannins, a defense-related compound, in phloem of asymptomatic and symptomatic trees. This work is the first to show that FT-IR spectroscopy can be used for the identification of Norway spruce trees naturally infected with Heterobasidion spp.